High-Throughput DNA Metabarcoding for the Gut Microbiome Assessment of Captive White-Handed Gibbon and Siamang - Badrul Munir, Md Zain; Wan Ainin Sofiya, Wan-Mustafa; Roberta Chaya Tawie, Tingga; Millawati, Gani; Mohd Ridwan, Abd Rahman (John Wiley & Sons Ltd., 2025)
The gut microbiota plays a vital role in primates' overall health and well-being, including small apes (Hylobatidae). The symbiotic relationships between bacteria and the gut aid food digestion, maintain host health, and help them adapt to their environment, including captive conditions. Despite being listed as endangered in the International Union for Conservation of Nature (IUCN) red list category, molecular studies on the small ape's gut microbiome are limited compared to other primates. This study aimed to characterize the gut microbiota of captive small apes at Zoo Taiping and Night Safari, Peninsular Malaysia, by evaluating their microbial communities. Seven fecal samples from Hylobatidae (white-handed gibbon and siamang) were collected, and the bacteria therein were successfully isolated and subjected to high-throughput sequencing of the 16S rRNA gene.The acquired amplicon sequence variants (ASVs) were successfully classified into 17 phyla, 82 families, 164 genera, and 43 species of microbes. Each small ape exhibited a unique gut microbiota profile. The phyla Bacteroidota and Firmicutes were dominant in each individual. Environmental conditions and host genetics are among the factors that influence the small ape's gut microbiome composition.These findings provide valuable insights into the gut microbiota composition of small apes at Zoo Taiping and Night Safari, thus contributing to the health management and welfare efforts of small apes in captivity